New correlation for vapor cloud explosion overpressure calculation at congested configurations - Li, Jingde; Abdel-jawad, M.; Ma, G. (Elsevier, 2014)
In this study, we present a newly developed correlation for the estimation of boundary overpressures in and around congested regions subjected to vapor gas explosions. The GAME correlation, which is based on the MERGE, EMERGE experimental programs, shows rather moderate correlation with computational fluid dynamics (CFD) results in homogeneously congested configurations, however, a greater level of inaccuracy is found when it comes to the combination of a number of realistic scenarios. The newly developed model (confinement specific correlation), which consists parameters of volume blockage ration, the density of the gas, the flame path distance, the confinement ratio and the laminar flame speed of the flammable gas is proposed as a non-dimensional alternative and it shows a closer correlation with detailed CFD simulation in general particularly for realistic geometries. A linear least square method is used to achieve the best fitting parameters by applying the validated commercial software FLACS. About 400 CFD cases with homogenous congestions are modeled using FLACS for the purpose of testing both the GAME correlation and the confinement specific correlation (CSC). In addition to those 400 CFD homogenous cases, around 700 realistic cases in ten different module scenarios of a Liquefied Natural Gas (LNG) train along with three simplified models are simulated to validate the CSC; it is found that the CSC is applicable to both realistic modules with irregular obstacles and homogenous artificial modules. © 2014 Elsevier Ltd.